PENGARUH RETURN ON ASSETS, RETURN ON EQUITY, DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PERBANKAN YANG GO PUBLIK DI BURSA EFEK INDONESIA - Uswatun Hasanah; Ita Purnama (Pusat Riset dan Publikasi, 2022)
This research was conducted to determine the effect of Net Interest Margin (NIM), Non Performing Loan (NPL) on Return On Assets (ROA) either partially or simultaneously at PT. Bank Rakyat Indonesia (Persero), Tbk, 2010-2019 Period. The research method is using the associative method, with a quantitative approach. Data collection techniques using secondary data. The population in this study is 16 years old and the sample used is 10 years which is the annual report of the banking sector on the Indonesia Stock Exchange (IDX). The sampling technique used purposive sampling technique. The results of the study using the t test and f test showed that partially Net Interest Margin (NIM), had a positive and significant effect on Return On Assets (ROA). Non-Performing Loans (NPL) are partially significant and have a negative and significant effect on Return On Assets (ROA). And simultaneously Net Interest Margin (NIM), and Non Performing Loan (NPL) have a significant positive effect on Return On Assets (ROA).